2019
DOI: 10.15408/a.v6i2.11365
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Management and Arabic Learning Process Based on Multiple Intelligences in Elementary School

Abstract: This study addressed to explore classroom management and Arabic Learning process based on Multiple intelligences theory implemented by the teacher. The study was a case study with descriptive qualitative approach. The data were collected by interview, documentation, and observation. Then, the data were analyzed with the following steps: data collection, data reduction, data display, verification, and affirmation conclusions. The result of this study revealed that the students were classified based on their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
1
10
0
2
Order By: Relevance
“…Some of these media support the learning of listening skills. Students' listening skills are influenced by the internal motivation that needs to be improved, the drive to use Arabic well, adequate facilities, the environment, and lecturers as examples (Swathi et al 2018;Mahmudi et al 2019;Cook, 2019). Repetition of material can provide encouragement for students to achieve learning goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these media support the learning of listening skills. Students' listening skills are influenced by the internal motivation that needs to be improved, the drive to use Arabic well, adequate facilities, the environment, and lecturers as examples (Swathi et al 2018;Mahmudi et al 2019;Cook, 2019). Repetition of material can provide encouragement for students to achieve learning goals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examine the students' perceptions of Arabic online learning and identify the strategies used. This is because the students' psychological conditions, the motivation, the learning environment, and their perceptions determine success (Guo, 2018;Saptenno et al 2019;Fong et al 2017;Mahmudi et al 2019;Islam et al 2019). Similarly, the use of different strategies may facilitate achieving set goals (Barnabas et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first fold was to incorporate the MI theory into the design and development of teaching and learning activities for primary school learners. Research goals were to develop activities suitable for each MI type, to develop learners' skills, and to examine learners' ability to perform learning activities [10,11,[18][19][20][21][22][23][24]. The second fold was to develop models and procedures for learning activities based on the principle of MI.…”
Section: Multiple Intelligence (Mi)mentioning
confidence: 99%
“…Prior research works can be classified into three approaches of learning activities: scenario and environment, off-class learning, and media-assisted learning as shown in Table 1. [20]   N. K. Maccario [21]  P. Polsombat [11]  S. T. Selvi [22]   T. Jommanop and S. Mekruksavanich [23]  P. Garmen et al [24] …”
Section: Multiple Intelligence (Mi)mentioning
confidence: 99%
“…Another data indicated that classroom was not only the class for learning, sometimes the teacher challenged the students to study outdoor, school environment. The school environment and facilities contributed to support learning process and give the students more space to be creative and aware with what they found in the school environment (Mahmudi, et al, 2019). In addition, research on learning innovations using a system of multiple intelligences has been applied by classifying students based on their dominant intelligence which is more effective (Truong, 2016).…”
Section: Multiple Intelligences Chartmentioning
confidence: 99%